Antibacterial poly (3, 4-ethylenedioxythiophene):poly(styrene-sulfonate)/agarose nanocomposite hydrogels with thermo-processability and self-healing. (1st January 2019) - Ko, Youngsang; Kim, Jeonghun; Jeong, Ho Young; Kwon, Goomin; Kim, Dabum; Ku, Minhee; Yang, Jaemoon; Yamauchi, Yusuke; Kim, Hae-Yeong; Lee, Chanhui; You, Jungmok
Highlights: PEDOT:PSS/agarose composite was developed as a photothermal material. A simple aqueous solution-based process was used to fabricate composite hydrogel. The composite hydrogel exhibited excellent antibacterial activity. Abstract: Recently, Near-infrared (NIR)-induced photothermal killing of pathogenic bacteria has received considerable attention due to the increase in antibiotic resistant bacteria. In this paper, we report a simple aqueous solution-based strategy to construct an effective photothermal nanocomposite composed of poly(3, 4-ethylenedioxythiophene):poly(styrene-sulfonate) (PEDOT:PSS) and agarose with thermo-processability, light triggered self-healing, and excellent antibacterial activity. Our experiments revealed that PEDOT:PSS/agarose was easily coated on both a 2D glass substrate and 3D cotton structure. Additionally, PEDOT:PSS/agarose can be designed into free-standing objects of diverse shape as well as restored through an NIR light-induced self-healing effect after damage. Taking advantage of strong NIR light absorption, PEDOT:PSS/agarose exhibited a sharp temperature increase of 24.5 °C during NIR exposure for 100 s. More importantly, we demonstrated that the temperature increase on PEDOT:PSS/agarose via photothermal conversion resulted in the rapid and effective killing of nearly 100% of the pathogenic bacteria within 2 min of NIR irradiation.